Transaksi Bank Syariah Dengan Non Muslim Ditinjau Dari Hukum Ekonomi Syariah - Khodijah, Siti; Hsb, Putra Halomoan; Lubis, Ihsan Helmi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research examines the legal review of Islamic economic law regarding transactions between Islamic banks and non-Muslims in Pasar Sipirok village in South Tapanuli Regency. The background of this research is based on the observation that the cultural characteristics of Non-Muslims, which often include a lack of cooperation, along with the capitalist spirit commonly associated with Non-Muslims, should make conventional banks, which operate under a capitalist system, a promising investment avenue. However, in reality, a significant number of Non-Muslim customers are also interested in saving their funds in Islamic banking. In the Sipirok market village, the residents are not only Muslims but also non-Muslims. Among those who use Islamic banking services, there are 60 people, 10 of whom are non-Muslims. This research is a field study with a qualitative approach from the perspective of Islamic economic law. The data sources in this study consist of two types: primary data and secondary data sources. The data collection techniques in this research are observation, interviews, and documentation. The data analysis technique used by the researcher in this study is inductive qualitative analysis. The research findings indicate that the views of non-Muslims towards Bank Syariah Indonesia are very positive, as it is a bank that shows tolerance towards non-Muslim customers without discriminating based on religion. It represents an opportunity for growth, as the use of contracts from Bank Syariah Indonesia by non-Muslims can be seen as a chance to develop and understand Islamic financial principles. Non-Muslims experience the services and conveniences provided, so it is not surprising that some non-Muslims choose Islamic banks for their savings and other needs. There are three factors that attract non-Muslims in the village of Pasar Sipirok to use products from Bank Syariah Indonesia: promotion, service, and service reputation.